Adolescent Pregnancy Outcome in a District Hospital of Bangladesh - Chowdhury, Nowshafreen; Rahim, Riffat; Khan, Laila Nazneen; Sweety, Kamrunnahar; Akther, Pervin (Mugda Medical College Journal, 2023)
Background: Adolescent pregnancy is universally accepted as high risk pregnancy. Bangladesh has the highest (1 in 10) adolescent fertility rate in South Asia. Objective: The study was conducted to find out the common problems of adolescent pregnancy. Methodology: A comparative cross-sectional study was carried out among 100 respondents (50 adolescents and 50 adults) in Munshigonj General Hospital from 1st January to 31st December 2018. Respondents were admitted patients who have delivered either vaginally or by caesarian section. Women aged 15 to 19 years selected as adolescent and those aged 20 to 40 years selected as adult. Socio-demographic characteristics, past obstetric history, antenatal checkup, antenatal and intrapartum complications, and clinical state on admission were recorded in a semi structured questionnaire. Obstetrical parameters of adolescent and adult groups were compared. Results: Among total admitted patients 11% were adolescent. 70% were from rural area, 68% were poor, 50% didn’t have even primary education, 92% adolescent never use contraceptive, 56% had no ANC. Anemia (62%) and hypertension (24%) were prevalent among the pregnant adolescents. Complication rate were more in adolescent group, like preeclampsia (12%), eclampsia (14%), preterm labor (12%), prolonged labor (14%), obstructed labor (8%). Caesarean rate was higher (66%) in adolescent pregnancy. Conclusion: Majority of the adolescents had no ANC, complication rate were more prevalent in adolescent group. Adverse perinatal outcome was found in adolescent pregnancy. Mugda Med Coll J. 2022; 5(2): 55-59